HUBUNGAN ANTARA SELF REGULATION DENGAN RESILIENSI DALAM MENYELESAIKAN SKRIPSI PADA MAHASISWA AKHIR PROGRAM STUDI AGAMA ISLAM FAKULTAS AGAMA ISLAM UNIVERSITAS ISLAM MALANG - Nadya Syarifah Al Madinah; Anwar Sa’dullah; Bagus Cahyanto (Vicratina : Jurnal Ilmiah Keagamaan, 2022)
Graduating in a short time is definitely the desire of every student. Common problems that are often faced by students in writing theses include not being able to run the scheduled thesis writing system, not being confident in themselves, and the low level of student interest in research. These difficulties can lead to stress, increased feelings of low self-esteem and frustration and loss of motivation. This research was conducted at the Islamic University of Malang. This study uses a quantitative approach. Data collection methods used are observation, questionnaires, and documentation. The data analysis technique in this study, the researcher used quantitative descriptive analysis, while the data analysis technique used to test the hypothesis in this study was correlation analysis. The results showed that: 1. The level of self-regulation in students of the Islamic Education Study Program, Faculty of Islamic Religion, Islamic University of Malang was in the high category with a percentage reaching 84.6%. 2. The level of resilience in students who are working on thesis at the students of the Islamic Religious Education Study Program, Faculty of Islamic Religion, Islamic University of Malang is in the high category as well, with a percentage of 84.7%. 3. There is a positive relationship between self-regulation and resilience.